الأحاديث الواردة في العزلة رواية ودراية - تركي, احمد; طليبة, جلال; شيخة مبروك, يوسف (University of Eloued-جامعة الوادي, 2022)
"ملخص المذكرة بالعربية * تمحورت هاته الدراسة الموسومة بالأحاديث الواردة في العزلة رواية ودراية حول اشكال رئيس وهو ما هي الأحاديث التي وردة في السنة النبوية حول موضوع العزلة وما مدى صحتها نقلا-دراية- وما الذي يمكن ان نيتنبط منها من الناحية العملية –رواية- ,لتأتي هاته الدراسة مجيبة عن هذا الاشكال من خلال أربعة وهي الأول منهما نظري والباقي تطبيقي. فأما بخصوص المبحث الأول النظري فقد جاء فيه تصور مفهوم العزلة كمصطلح من النواحي اللغوية والشرعية وما مدى وجوده في التراث الاسلامي وكذلك في العلوم العصرية –الانسانية والاجتماعية والنفسية – أما المبحثين الثالث والرابع فكانا تطبيقين للأحاديث التي وردت في العزلة من ناحية المدح والذم وما مدى صحتها وقد تم فيهما جرد عدد لا بأس به من الأحاديث في هذا الموضوع وتمت دراستها رواية ودراية . أما المبحث الرابع فقد تطرقنا فيه الى الموقف الشرعي الصحيح من العزلة بين المدح والذم والتوفيق بين القولين ,وكذلك التطرق الى أهم أنواع العزلة وضوابطها. ولقد ختمت هاته الدراسة بجملة من النتائج منها أن العزلة وفق الضوابط الشرعية هي من أبرز العلاجات النفسية التي أتى بها الشرع الحنيف, بالاضافة الى بعض التوصيات التي من أبرزها تكريس العناية بموضوع العزلة والخلوة والاعتكاف النبوي وكل ما يتعلق بهذا النوع من العبادات ."" This study, which is tagged with the hadiths contained in Solitude, revolved around a narration and knowledge about major forms, which are the hadiths that were mentioned in the Prophetic Sunnah on the subject of isolation, and how true they are in quotation - knowledge - and what we can derive from them from a practical point of view - a narration -, so that this study comes an answer about There are four forms of this, the first of which is theoretical and the rest is practical. As for the first theoretical topic, it came in which to visualize the concept of isolation as a term from the linguistic and legal aspects, and the extent of its presence in the Islamic heritage as well as in the modern sciences - human, social and psychological - As for the third and fourth sections, they were applications of the hadiths that were mentioned in solitude in terms of praise and slander, and how true they are. In them, a good number of hadiths on this subject were inventoried, and they were studied with narration and knowledge. As for the fourth topic, we discussed the correct legal position on isolation between praise and slander and reconciling the two sayings, as well as touching on the most important types of isolation and its controls. This study was concluded with a number of results, including that isolation according to Shariah controls is one of the most prominent psychological treatments brought by the true Sharia, in addition to some recommendations, the most prominent of which are devoting care to the issue of isolation, solitude, the Prophet’s i’tikaf and everything related to this type of worship."
مذكرة ماستر
Keywords: العزلة -مدح العزلة -ذم العزلة - احاديث العزلة; Solitude - praise of solitude - censure of solitude - talk of solitude